Messy data missing observations, outliers, and mixed-frequency data - Hill, R. Carter (Advances in econometrics ;, 1999)
Often applied econometricians are faced with working with data that is less than ideal. The data may be observed with gaps in it, a model may suggest variables that are observed at different frequencies, and sometimes econometric results are very fragile to the inclusion or omission of just a few observations in the sample. Papers in this volume discuss new econometric techniques for addressing these problems.